2013
DOI: 10.1186/1471-2407-13-533
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profile in head and neck cancer: HOX-cluster embedded microRNA-196a and microRNA-10b dysregulation implicated in cell proliferation

Abstract: BackgroundCurrent evidence implicates aberrant microRNA expression patterns in human malignancies; measurement of microRNA expression may have diagnostic and prognostic applications. Roles for microRNAs in head and neck squamous cell carcinomas (HNSCC) are largely unknown. HNSCC, a smoking-related cancer, is one of the most common malignancies worldwide but reliable diagnostic and prognostic markers have not been discovered so far. Some studies have evaluated the potential use of microRNA as biomarkers with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 54 publications
4
46
0
4
Order By: Relevance
“…Unlike in some cancers, its role in HNSCC is unclear (63). We found a large functional hypermethylated DMR around miR-10B spanning several megabases ( Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Unlike in some cancers, its role in HNSCC is unclear (63). We found a large functional hypermethylated DMR around miR-10B spanning several megabases ( Fig.…”
Section: Discussionmentioning
confidence: 82%
“…miR-196a is a known onco-miRNA that plays an important role in tumorigenesis and tumor progression (Peng et al, 2010;Sun et al, 2012). Emerging evidence suggests the aberrant over-expression of miR-196a is a frequent event in various cancers, including head and neck squamous cell carcinomas (Severino et al, 2013), laryngeal cancer (Saito et al, 2013), pancreatic cancer (Liu et al, 2013), and gastric cancer (Tsai et al, 2012). It has been reported that over-expression of miR-196a is associated with apoptosis, invasion, and proliferation in pancreatic cancer (Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The first identified targets of miR‐196a were HOXA and HOXB genes in primary adult acute myeloid leukaemia, and HOXC8 and HOXB7 in malignant melanoma . However, HOX genes have not been shown to be regulated by miR‐196a in head and neck cancer cell lines such as SCC25 and FaDu . Other validated targets of miR‐196a include annexin A1 (ANXA1), S100A9, SPRR2C and KRT5 in oesophageal cancer cells, and ERG in leukaemia, but the precise roles of these targets in regulating the oncogenic effects of miR‐196a so far remain unclear.…”
Section: Introductionmentioning
confidence: 99%